Flow cytometric DNA studies and AgNOR counts in patients with transitional cell carcinoma of the bladder - ÇELİKEL, ÇİĞDEM (My University, 1995)
Flow cytometry appears to be a promising diagnostic method which may influence the therapeutic approach to transitional cell carcinoma (TCC) of the bladder. The number of silver-stained nuclear organizer regions (AgNORs) seems to correlate with the growth fractions of the cells. In this study, we report the results of combined flow cytometric analysis and AgNOR in 37 patients with TCC of the bladder. A positive correlation was observed in the histological grade, stage and growth pattern in relation to the ploidy of tumors. There were statistically significant differences among the mean AgNOR counts of the different groups as defined by DNA content, histological grade, growth pattern and disease outcome. In different stage groups, the AgNOR counts were related both to recurrence and progression. It was concluded that AgNOR counts performed on routine formalin-fixed paraffin sections furnish significant kinetic information. According to our preliminary results AgNOR counts and the DNA content of the tumors should also be measured to decide on more aggressive treatment in some cases.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; Üroloji; Urology; AgNOR; Bladder neoplasms; DNA cytometry; Flow cytometry